Reseña/Review (Benasayag, M., del Rey. A. "Nunca más solo. El fenómeno del móvil", Madrid: Editorial La Oveja Roja, ISBN: 978-84-935829-2-0, 116 págs., 2009) - Domínguez, David Jorge (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2012)
Reseña/Review (Benasayag, M., del Rey. A. "Nunca más solo. El fenómeno del móvil", Madrid: Editorial La Oveja Roja, ISBN: 978-84-935829-2-0, 116 págs., 2009)